THE PROBLEMS AND CHALLENGES OF CHILDREN FROM MULTICULTURAL FAMILIES IN SOUTH KOREA - Kim Jang Gyem (Puitika)
In this article, the problems and challenges of children from multicultural families in South Korea are described. The research subjects were the children (preschool-elementary school ages) from multicultural families (Korean and Indonesian) who settled in Korea. The objects of this qualitative study are the problems and challenges that they face. The data obtained are described and analyzed and then presented with descriptive methods. The problems faced by the children of multicultural families are generally more to the Indonesian culture. They almost did not get the problems with the Korean social and culture life because they grow and develop in Korean social society and culture. They can overcome some of the differences and difficulties with the help of social institutions provided by the Korean government for multicultural families. Thus, the challenge that they face is to equally understand both of their background cultures, the Korean and Indonesian.